Person‐centred, web‐based support in pregnancy and early motherhood for women with Type 1 diabetes mellitus: a randomized controlled trial. Issue 2 (12th December 2017) - Linden, K.; Berg, M.; Adolfsson, A.; Sparud‐Lundin, C.
Abstract: Aims: To report results from and explore use of a multicentre, parallel‐group, unblinded, randomized controlled trial testing the effectiveness in terms of well‐being and diabetes management of a person‐centred, web‐based support programme for women with Type 1 diabetes, in pregnancy and postpartum. Methods: Between 2011 and 2014, 174 pregnant women with Type 1 diabetes were randomly allocated (1:1) to web‐based support and standard care (intervention group, n =83), or standard care (control group, n =91). The web‐based support consisted of evidence‐based information; a self‐care diary for monitoring of daily activities; and peer support in a discussion forum. The primary outcomes (mean difference, measured at 6 months after childbirth) were well‐being and diabetes management. Results: No differences were found with regard to the primary outcome measure scores for general well‐being [1.04 (95% CI –1.28 to 3.37); P =0.68] and self‐efficacy of diabetes management [0.08 (95% CI –0.12 to 0.28); P = 0.75], after adjustment for baseline differences in the insulin administration method, nor with regard to the secondary outcome measures. Conclusions: At 6 months after childbirth, the web‐based support plus standard care was not superior to standard care in terms of general well‐being or self‐efficacy of diabetes management. This might be explained by the low number of participants who had a high activity level. Few simultaneously active participants in the web‐based programme and stressors in motherhood and diabetes postpartum were the main barriers to its use. Further intervention studies that offer web‐based support are needed, with lessons learned from the present study. (Clinicaltrials.gov identification number: NCT015665824) What's new?: This randomized controlled trial of 174 women with Type 1 diabetes mellitus evaluated a person‐centred, web‐based support programme aimed at improving the well‐being and self‐efficacy of diabetes management during pregnancy and after childbirth, with the primary endpoint being at 6 months after childbirth. No significant differences were found between the intervention group receiving the web‐based support and standard care, and the control group receiving standard care. The main barriers to the use of the web‐based support were the low number of simultaneously active participants as a result of the randomization rate, and the high demands in daily life after childbirth in caring for the baby and their diabetes.